(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper investigates novel properties of Hilbert spaces through tensor operations and establishes new bounds for Simpson-type inequalities using fractional integral operators. The results contribute to advancing the theoretical understanding of these mathematical structures and their applications in functional analysis and related fields.